Theory, phenomenology, and experimental avenues for dark showers: a Snowmass 2021 report - Albouy, Guillaume; Barron, Jared; Beauchesne, Hugues; Bernreuther, Elias; Bona, Marcella; Cazzaniga, Cesare; Cesarotti, Cari; Cohen, Timothy; de Cosa, Annapaola; Curtin, David; Demiragli, Zeynep; Doglioni, Caterina; et al. (The European physical journal. C, Particles and fields, 2022)
Abstract - - In this work, we consider the case of a strongly coupled dark/hidden sector, which extends the Standard Model (SM) by adding an additional non-Abelian gauge group. These extensions generally contain matter fields, much like the SM quarks, and gauge fields similar to the SM gluons. We focus on the exploration of such sectors where the dark particles are produced at the LHC through a portal and undergo rapid hadronization within the dark sector before decaying back, at least in part and potentially with sizeable lifetimes, to SM particles, giving a range of possibly spectacular signatures such as emerging or semi-visible jets. Other, non-QCD-like scenarios leading to soft unclustered energy patterns or glueballs are also discussed. After a review of the theory, existing benchmarks and constraints, this work addresses how to build consistent benchmarks from the underlying physical parameters and present new developments for the - pythia - Hidden Valley module, along with jet substructure studies. Finally, a series of improved search strategies is presented in order to pave the way for a better exploration of the dark showers at the LHC.
Gesehen am 23.03.2023